Peningkatan Keterampilan Bernyanyi dengan Pendekatan Teknik Vokal pada Siswa Kelas VI di Sekolah Dasar Negeri 173632 Porsea - Alfrando Sinaga; Theo Salf Lase; Theresia Gurning; Dwi Putri A. Br. Nababan; Sopan Sopian Purba; Parsaoran Silalahi (Jurnal Kemitraan Masyarakat, 2025)
This study aims to improve the singing skills of sixth grade students at State Elementary School 173632 through the national song "Indonesia Raya". application of vocal techniques. This study uses a quantitative descriptive approach with a classroom action research (CAR) method approach which is carried out in several cycles, including the stages of planning, implementation of actions, observation, and reflection. The results of the study indicate that the systematic application of vocal techniques can improve the quality of students' singing. Diaphragm breathing exercises help students control their voices more stably, articulation techniques make song lyrics clearer, intonation exercises improve pitch accuracy, and expression techniques help students convey emotions in songs better. Data analysis shows an increase in the average singing skills of students from the category of sufficient to good after being given action. In addition, the results of observations show that the majority of students feel more confident and enjoy learning to sing with a vocal technique approach. Thus, this study can help improve students' vocal skills as well as knowledge for students and teachers as well as for readers.